Epithelial CD47 is critical for mucosal repair in the murine intestine in vivo - Michelle Reed (Nature Portfolio, 2019)
The role of the transmembrane glycoprotein CD47 in healing injured intestinal mucosa is unclear. Here, the authors show that selective loss of CD47 in the murine intestinal epithelium results in defective mucosal repair after colonic wounding, with suggested impaired cell migration in vitro.